2021
DOI: 10.4049/immunohorizons.2000067
|View full text |Cite
|
Sign up to set email alerts
|

Tissue-Resident Memory T Cells in the Lungs Protect against Acute Respiratory Syncytial Virus Infection

Abstract: Respiratory syncytial virus (RSV) is the leading cause of lower respiratory tract infection in young children. The T cell response plays a critical role in facilitating clearance of an acute RSV infection, and memory T cell responses are vital for protection against secondary RSV exposures. Tissue-resident memory (TRM) T cells have been identified as a subset of memory T cells that reside in nonlymphoid tissues and are critical for providing long-term immunity. There is currently limited information regarding … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
46
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 44 publications
(48 citation statements)
references
References 55 publications
2
46
0
Order By: Relevance
“…Similarly, influenza-specific CD8 + Trm in human lung tissue wane with advanced age, and this resulted in a lag in the development of an antiviral response following influenza exposure 95 . The attrition of lung CD8 + Trm is not restricted to influenza-specific Trm cells, as similar findings are observed following Sendai virus 116 , 118 and RSV 101 infections in mice. Although murine lung CD4 + CD69 + Trm also decline, their decay is less rapid relative to CD8 + Trm 18 , 51 , 119 .…”
Section: The Persistence Of Respiratory Tract Trmsupporting
confidence: 82%
See 1 more Smart Citation
“…Similarly, influenza-specific CD8 + Trm in human lung tissue wane with advanced age, and this resulted in a lag in the development of an antiviral response following influenza exposure 95 . The attrition of lung CD8 + Trm is not restricted to influenza-specific Trm cells, as similar findings are observed following Sendai virus 116 , 118 and RSV 101 infections in mice. Although murine lung CD4 + CD69 + Trm also decline, their decay is less rapid relative to CD8 + Trm 18 , 51 , 119 .…”
Section: The Persistence Of Respiratory Tract Trmsupporting
confidence: 82%
“…Using an elegant experimental human challenge model, Jozwik et al 99 identified RSV-specific CD8 + Trm in the airways and showed that high numbers of virus specific airway CD8 + Trm, but not virus specific circulating blood T cells, correlated with less-severe lower respiratory tract symptoms and reduced viral loads post RSV challenge. Subsequent murine studies corroborate this data and show that airway and parenchyma CD8 + T cells protect against secondary RSV infection 100 , 101 .…”
Section: The Protective Capacity Of Respiratory Tract Trmmentioning
confidence: 70%
“…CD4+T RM cells and CD8+T RM cells T RM cells showed gradual differentiation with down-regulated costimulatory molecules and increased CXCR3 expression, which had been implicated in protection against RSV-induced lung pathology in mice via dendritic cells and CD8+ T cells. (43)(44)(45) Bordetella Pertussis CD69+CD4+T RM cells T RM cells produced IL-17 and IFN-g, thereby recruiting neutrophils and preventing their colonization in the nose. (46)(47)(48)(49) Influenza Viruses…”
Section: Respiratory Syncytial Virusmentioning
confidence: 99%
“…Virus-specific memory T cells correlate with protection from RSV infection and are critical for reducing disease pathogenesis, making them an important population to induce through vaccination [48][49][50]. RSV-specific cellular immune responses are impaired in both their number and functional capacity in elderly adults.…”
Section: Defects In Cellular Immunitymentioning
confidence: 99%